2020
DOI: 10.1029/2020jg005793
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature and Light on Methane Production of Widespread Marine Phytoplankton

Abstract: Methane (CH 4) production in the ocean surface mixed layer is a widespread but still largely unexplained phenomenon. In this context marine algae have recently been described as a possible source of CH 4 in surface waters. In the present study we investigated the effects of temperature and light intensity (including daylength) on CH 4 formation from three widespread marine algal species Emiliania huxleyi, Phaeocystis globosa, and Chrysochromulina sp. Rates of E. huxleyi increased by 210% when temperature incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 96 publications
(146 reference statements)
1
24
1
1
Order By: Relevance
“…The waters around the East Frisian islands (south from our study area) are known for a predominant anaerobic degradation of organic matter (Schwichtenberg et al, 2020), which could lead to a small water mass associated with low oxygen and high methane content. (2) The aerobic CH 4 production by marine phytoplankton (Lenhart et al, 2016;Klintzsch et al, 2020); however, it is unknown if this occurs in our study area. (3) The aerobic CH 4 production from microbial decomposition of certain organic phosphorus compounds (Karl et al, 2008;Repeta et al, 2016).…”
Section: Single Factors (Water Mass Origin Oxygen Turbidity)mentioning
confidence: 95%
“…The waters around the East Frisian islands (south from our study area) are known for a predominant anaerobic degradation of organic matter (Schwichtenberg et al, 2020), which could lead to a small water mass associated with low oxygen and high methane content. (2) The aerobic CH 4 production by marine phytoplankton (Lenhart et al, 2016;Klintzsch et al, 2020); however, it is unknown if this occurs in our study area. (3) The aerobic CH 4 production from microbial decomposition of certain organic phosphorus compounds (Karl et al, 2008;Repeta et al, 2016).…”
Section: Single Factors (Water Mass Origin Oxygen Turbidity)mentioning
confidence: 95%
“…Their production rates of 0.7 and 3.1 μg CH 4 g −1 POC d −1 , respectively, from cultures in an exponential growth phase, are much lower than our rate of 2.56 μg CH 4 g −1 POC h −1 due to our higher measured POC values. Subsequently, Klintzsch et al (2020) showed that the level of PAR could control CH 4 production by over an order of magnitude and was increased by continuous illumination compared to a 6/18h light cycle. Microbial degradation of DOM phosphonates was shown to produce CH 4 and C 2 H 4 by Repeta et al (2016), Perez-Coronel and Beman (2020), and Sosa et al (2020), while Bižić et al (2020) reported CH 4 production from metabolism of 17 marine, freshwater, and terrestrial cyanobacteria (independent of methylated precursors e.g., methylphosphonate).…”
Section: Methane Productionmentioning
confidence: 99%
“…Their production rates of 0.7 and 3.1 μg CH4 g -1 POC d -1 respectively, from cultures in an exponential growth phase, are much lower than our rate of 2.56 μg CH4 g -1 POC h -1 due to our higher measured POC values. Subsequently, Klintzsch et al (2020) showed that the level of PAR could control CH4 production by over an order of magnitude and was increased by continuous illumination compared to a 6/18h light cycle.…”
Section: Accepted Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Examples include ice algae and phytoplankton, such as some Phaeocystis, which produce dimethylsulfoniopropionate (DMSP) and thereby have a negative effect on global warming [1][2][3]. By contrast, some species of archaea, bacteria, microalgae and protozoa can produce methane (CH 4 ) [4][5][6][7][8] and greenhouse gases, such as CO 2 (through biological respiration), which contributes to global warming. So even though these organisms are small, their functions are not insignificant.…”
Section: General Description Of Microorganismsmentioning
confidence: 99%